Essential readings in Islamic finance - Bakar, Mohd Daud (CERT Publications Sdn. Bhd., 2008)
This "Essential Readings in Islamic Finance" is a collection of separately written papers that had been presented in various workshops and seminars. The authors of these papers are prominent figures from diferent backgrounds and are well known in their area of expertise. This book contains a total of twenty-two papers falling under the five themes, i.e, Shari`ah Framework of Islamic Banking and Finance; Islamic Banking Development; Takaful (Islamic Insurance); Legal, Accounting and Governance in Islamic Finance and Islamic Capital Market. This book gives an overview of the practice of Islamic finance, and highlights the latest developments in this innovative and fast-growing industry. Some of the papers also analyze the specific practicalities of contemporary financial instruments within the Shari'ah compliance framework. The book also discusses the challenges faced by Islamic finance industry and proposes suggestions for the way forward. We hope that the information provided in this book will be useful and enlightening to all scholars, researchers, students, academicians and practitioners.